Integrated Construction Process for Green Building. (2016) - Ahn, Yong Han; Jung, Chan Woo; Suh, Minjae; Jeon, Myung Hwa
Abstract: Green Building is rapidly becoming a strong momentum in the construction industry after recognizing many negative environmental issues & problems and potential social and economical benefits. In green building, all stakeholders including an architect, a contractor, engineers, etc. need to collaborate to successfully complete integrated green design and construction that can eventually achieve the goals of sustainability in construction. Since there are many negative environmental issues and problems as well as many opportunities, it is very important to develop an Integrated Construction Process (ICP) f that can help all stakeholders to successfully implement green building strategies and technologies at the construction phase of the project development. Thus, this study develops an 'ICP' including goals of green construction processes, step-by-step procedure, the roles and responsibilities of three main stakeholders such as an architect, a contractor, and subcontractor that can help all stakeholder to achieve sustainability at the construction phase.